Corporate financial risks: Is there a role of insider incentives? - Satrio, Arif Budi (MBR (Management and Business Review), 2023)
Weak corporate governance in developing countries, the complexity of agency issues, and the lack of consensus on insider and corporate financial risk relations are the reasons why this issue is urgent to investigate. This study investigates the role of insider incentives on corporate financial risk with a sample of 234 non-financial companies in Indonesia for 2003-2018 using dynamic system GMM panel regression, taking into account the number of fundamental factors and firm-level characteristics in the test. Robust findings show that insiders significantly reduce firms' financial risk, and this effort became even more evident after the 2008 subprime crisis. These findings clarify agency issues in firms in developing countries and support the pecking order theory. These findings enrich the literature, especially regarding good corporate governance, and are helpful for regulators regarding regulations, especially in developing countries.